Rodrigo de Souza Leão : esquizofrenia e literatura na composição da Vida como Obra de Arte ( Rio de Janeiro 1985-2009) - Parteka, Thamara (2016)
Rodrigo de Souza Leão (1965-2009) was a writer and a plastic artist carioca that by the age of 23 (1989) was diagnosed with paranoid schizophrenia and obssessive compulsive disorder. Our work intended to discuss the ways of subjectivation of this writer and realize how he built an aesthetic way of ecxistence, lined mostly on literature. For that, in a first moment we investigated who this subject was before his crises and the diagnosis; in a second moment we seek to realize how Rodrigo dealt with the diagnosis and the disease, finally, we analyzed how he reframe this diagnosis after his second hospitalization (2001). For the research we bases mostly in literaly sources (autobiographical) writed by the author. Todos os Cachorros São Azuis (2008), O Esquizoide o Coração na Boca (2011), Carbono Pautado (2011), beside poetrys and various articles that are available ath the blog and oficial site of the author. We also use interviews of friends and relatives, some granted to us and others availables on internet and in the digital collection of the author on the Fundação Casa Rui Barbosa, beside some institutional documents like the Relatório da II Caravana Nacional dos Direitos Humanos (2002) and the website of Clinica da Gávea were he had been hospitalized